Towards a more human economy: technology in vital goods to reduce the cost of living (Journal of Business, Universidad del Pacífico (Lima, Peru), 2014)
This paper represents an essay that aims to propose guidelines applicable to the Peruvian economy to increase productivity in the production of vital goods (safe water, nutritious food, clothing and shelter) and services associated with them. According to the authors, these are indispensable to undertake any project of human life. In the application, examples of projects that would achieve the objective in Peru are presented. To do so, relevant geographical aspects, the development of energy infrastructure, transportation, water systems and a proposed development plan macro-regional were considered.
Keywords: vital goods; cost of living; economy and development of Peru